Neuroprotective Potential of Lithium Chloride in a Model of Traumatic Brain Injury - Denis T. Sharikadze; Mikhail V. Gabitov; Ivan V. Redkin; Artem N. Kuzovlev; Viktor V. Moroz (Общая реаниматология, 2023)
Aim: to investigate the neuroprotective properties of lithium chloride in a rat model of open traumatic brain injury (OTBI).Materials and Methods. An open traumatic brain injury (OTBI) model was induced using the D. M. Feeney method. The study included 40 male Wistar rats divided into four groups: sham-operated animals (sham, N=10); a OTBI control group (control, N=10); a group receiving lithium chloride at a dose of 1.5 mmol/kg after OTBI (OTBI + lithium 63 mg/kg, N=10); and a group receiving lithium chloride at a dose of 0.5 mmol/kg after OTBI (OTBI + lithium 21 mg/kg, N=10). Cognitive and neurological functions were assessed using the Morris water maze and the forelimb placing test. Brain lesion volume was assessed by magnetic resonance imaging (MRI) on day 14 post-injury.Results. Lithium chloride at 63 mg/kg administered 60 minutes after OTBI reduced brain lesion volume by 41.5% compared to the control group (P=0.001), while the 21 mg/kg dose reduced lesion volume by 27.5% (P=0.001). Lithium chloride at 63 mg/kg improved cognitive performance by 71% compared to the control group (P=0.009); the 21 mg/kg dose resulted in a 65% improvement (P=0.010).Conclusion. Lithium chloride at doses of 21 mg/kg and 63 mg/kg has neuroprotective properties, significantly reduces brain lesion volume (as confirmed by MRI), alleviates neurological deficits, and thereby improves cognitive function in animals after OTBI.